A brief review of studies on interpreters' ideological mediation/intervention at international conferences - Gao, Fei (Frontiers in Communication, 2022)
In interpreter-mediated international conferences, it is the interpreters' “voice” rather than the speaker's “voice” that is heard by world leaders. With a focus on the political discourse (re)produced at international conferences, this paper presents a brief review of relevant studies on interpreters' ideological mediation/intervention. The review starts with an introduction of related terminologies for ideological intervention in conference interpreting research (CIR). The review paper examines relevant studies in terms of (1) the international conferences as discursive events, (2) meeting/panel/speech topics as discourse topoi, and (3) interpreters' use of linguistic means to realize ideological shifts in the reconstructed discourse. The review concludes with a summary and gaps paralleled by future directions for CIR.